The Negative Photoconductivity of Ag/AgO Grown by Spray-Pyrolysis - Aline Bastos de Paiva; Luis Miguel Bolaños Vargas; Matheus José da Silva; Ariano De Giovanni Rodrigues; Demétrio A. W. Soares; Marcelos Lima Peres; Marcio Peron Franco de Godoy (Surfaces, 2022)
The main goal of this work is to provide a general description of the negative photoconductivity effect observed in Ag/AgO films grown by the spray-pyrolysis technique. X-ray diffractograms display hybrid films with high texturized AgO and metallic Ag phases. Scanning electron microscopy images show small Ag particles on the surface. Due to its surface nature, X-ray photoelectron spectroscopy revealed the predominance of the metallic character of Ag 3d spectra as compared to Ag2+. Negative photoconductivity with photoresponse in the order of seconds is observed under several wavelengths of excitation. We found that the amplitude of the negative photoresponse is strongly dependent on the optical absorbance and enhanced by surface plasmon resonance. The low-cost technique employed and the special features regarding negative photoconductivity provide an exciting platform for developing optical-electronic devices with low power consumption.